Self- Efficacy and Caregiver Strain in Alzheimer\'s Caregivers - Farahnaz Mohamadi Shahbalaghi (Sālmand, 2006)
This study with a co relational design has conducted to determine relationship between caregiving strain and self-efficacy in family caregiver of patient with Alzheimer. Accessible sample of the study consisted of 81 family caregivers that all of them were member of Iranian Alzheimer Association. Data was gathered by demographic, self-efficacy and care giving strain questioners. Findings showed the most of the subjects were female (%60), spouse of care giving recipient (56%), married (64%), reside in same household (55%), 49% under high school education, 45% of them haven't taken formal courses about the care of the patients, 53% of them were satisfied about providing of care, 36% reported bad health status. The most important caring needs consisted education for better care providing. the Mean of self-efficacy was 66/96 (29-106) and strain 39/43 (17-65). There were not any relations between strain and self-efficacy with demographic variables. There was positive significant Pearson correlation (r=0/539, p=O/ 01) between self-efficacy and strain. Findings indicated that self-efficacy and care giving strain are subjective and individualized concepts. Care giving to elderly patients is a stressful event but moderate co-relationship shows that caregivers apprise the stress of care giving as a constructive and controllable manner.